The effect of a proposed program in developing the fatigue index and some physical characteristics of football players U17 - والي عبد النور (sports creativity, 2025)
The main objective of this research is to study the impact of a proposed training program on the fatigue index, explosive power of the legs and speed of movement of football players (U17). We assumed that there are significant differences between the before and after tests for the two experimental and control samples for the after tests, the experimental method was used and the study was conducted on a sample of 12 players from the (OM) msila football, season 2020-2021. After the statistical treatment we come to There are significant differences for the proposed training program on the fatigue index and physical qualities (explosive power of the legs, speed of movement)